La frontière communautaire entre druzes et sunnites en Syrie - Cyril Roussel (EchoGéo)
In geography, border is a polysemic concept. In addition to its common (current) meaning which qualifies (describes) the lines which cut out the land space into state political entities, a geographer has to analyze all forms of limits, discontinuities and other divisions which partition human space. The Middle East, a multicultural and multi-community area, presents (offers) an exciting field to the study of socio-cultural phenomena and to their spatial effects. From the druze example in Syria, we shall show how a social border, the one built by the group itself, has generated a community territory delimited by well differentiated borders and how the last mentioned were used as a basis to the construction of political borders from the moment that the strategies of the successive ruling states in Syria converged with the socio-spatial construction produced by the Druze community.